GAMBARAN KESADARAN PERILAKU MASYARAKAT TERHADAP PEMBERANTASAN JENTIK NYAMUK DI DESA KELAMBIR KECAMATAN PANTAI LABU - NURUL RAHMAH SIREGAR; RIZKA SORAYA HASIBUAN; SRI WULAN HASIBUAN; SUHAILA ADZANA LUBIS; PUAN RIZKA; SYARIAH HILALIYAH PULUNGAN (JURNAL ILMIAH KOHESI, 2021)
Indonesia is one of the countries in Southeast Asia that is found the most dengue cases in 2009 were 156,052 cases (WHO, 2011). The presence of larvae Aedes aegypti mosquitoes cause dengue fever caused by the existence of the place water reservoirs that play a big role in the density of the Aedes aegypti mosquito vector, because the more adequate water reservoirs, the more places there will be larvae of the mosquito Aedes aegypti for breeding. This study aims to find out How is the knowledge, attitudes and actions of society with the presence of mosquito larvae Aedes aegypti in Tobuuha Village, Puuwatu District, Kendari City in 2016. Kind The research used in this study is descriptive using the method observational. The results of the study found that out of 100 respondents (100%) had good knowledge as many as 76 respondents (76%), lack knowledge as many as 24 respondents (24%), good attitude of respondents 70 respondents (70%), attitude less as many as 30 respondents (30%), less actions as many as 52 respondents (52%), have good action A total of 48 respondents (48%), 93 respondents had flicks and 7 respondents did not have larvae, it was concluded that knowledge was good and there were mosquito larvae as many as 73 respondents (73%), good attitude and flicks of 66 respondents (66%), and good actions and There were 44 respondents (44%).